2015
DOI: 10.1111/1911-3846.12214
|View full text |Cite
|
Sign up to set email alerts
|

Discussion of “Corporate Political Connections and Tax Aggressiveness”

Abstract: Kim and Zhang (2015) study the relation between corporate political connections and tax aggressiveness. In this discussion, I identify and evaluate three main limitations of their paper: the measurement of political connections, the empirical design, and the possible reasons behind the documented results. I build on these small shortcomings to provide suggestions for further contributions in this area of research. « Liens politiques des soci et es et audace de leurs positions fiscales » : une analyse critique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
3
15
0
3
Order By: Relevance
“…Similarly, the lagged ETR coefficients were positive and significant, confirming that there was dynamism in the model. Similar to earlier studies (e.g., Chen, Dyreng, & Li, 2015;Faccio, 2016;Hoopes, Mescall, & Pittman, 2012;Kim, Li, & Zhang, 2011;Kim & Zhang, 2016;Richter et al, 2009;Wilson, 2009), this study achieved the expected conclusion of a negative relationship and a dynamic Notes: The standard errors are reported in parentheses, except for the Hansen test, AR1, AR2, and Difference-in-Hansen test. ***, ** and * indicate significance at 1%, 5%, and 10% levels, respectively.…”
Section: Conditional Mean Regression Model-system Gmmsupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, the lagged ETR coefficients were positive and significant, confirming that there was dynamism in the model. Similar to earlier studies (e.g., Chen, Dyreng, & Li, 2015;Faccio, 2016;Hoopes, Mescall, & Pittman, 2012;Kim, Li, & Zhang, 2011;Kim & Zhang, 2016;Richter et al, 2009;Wilson, 2009), this study achieved the expected conclusion of a negative relationship and a dynamic Notes: The standard errors are reported in parentheses, except for the Hansen test, AR1, AR2, and Difference-in-Hansen test. ***, ** and * indicate significance at 1%, 5%, and 10% levels, respectively.…”
Section: Conditional Mean Regression Model-system Gmmsupporting
confidence: 83%
“…However, campaign contributions are not the only form of corporate political money involved, as the amount of money spent for lobbying purposes is substantially high (Kim & Zhang, 2016;Richter et al, 2009). Many empirical studies have shown that politically aligned firms are tax aggressive as they enjoy low detection risk, high risk-taking tendency, less corporate pressure for transparency, lower political costs associated with aggressive tax planning, and more information on future changes in tax regulation and enforcement (Barrick & Brown, 2016;Chen, Dyreng, & Li, 2015;Faccio, 2016;Martinez, 2017). Nevertheless, research on lobbying has neglected to investigate the issue of tax aggressiveness.…”
Section: Introductionmentioning
confidence: 99%
“…This causes conflict of interest between the director and the company owner in the context of taxation. Studies by reference [16] and [26] show the positive effect of director's political connection toward tax aggressiveness. Furthermore, research [30] explains that there are two sides in the relation between political connection and tax aggressiveness, which are political favoritism effect and bureaucratic incentive effect.…”
Section: A Political Connection Of Directors and Tax Aggressivenessmentioning
confidence: 98%
“…The use of ETR is based on some consideration. Firstly, ETR is one of tax aggressiveness parameters most often used in the study of tax aggressiveness (see [1], [9], [18], [16], [24], [27], [7], and [3]). Secondly, the approach of tax aggressiveness measurement using ETR can give the overall portrayal regarding the presence of tax expense change because it can represent the current tax value as well as the deferred tax [12].…”
Section: B Operational Definition and Variable Measurementmentioning
confidence: 99%
See 1 more Smart Citation